MUSIK GAMBANG KROMONG DALAM MASYARAKAT BETAWI DI JAKARTA - Soekotjo Soekotjo (Institut Seni Indonesia Yogyakarta, 2012)
The existence of Gambang Kromong music among Betawi people is well maintained. The traditional music has its own dynamics in the life of Betawi people. Betawi people expect that the traditional music could develop and be able to satisfy the musical tastes of its people by playing the composition with popular music and dangdut. It stimulates the creativity of the the traditional artists to combine the traditional music instrument of Grambang Kromong ensemble with Western music instruments. The dynamics of the traditional music results in the two categories of the Gambang Kromong, which are the genuine one and combined one. In spite of the dynamics, the supporting people of the traditional music remain to be faithful audience of the traditional ensemble that it is well-preserved up to the present time. Keywords: Gambang Kromong, Use and Function, Aesthetic, Society